Pelaksanaan Peran dan Fungsi embaga Saksi dan Korban di Indonesia Sesuai Undang-Undang Nomor 13 Tahun 2006 Tentang Perlindungan Saksi dan Korban (Lex Jurnalica, 2010)
In the process of disclosure of a criminal case from evidentiary court stage, the existence and role of the witness is expected. Even be the deciding factor and success in uncovering the criminal case. Without the presence and role of the witness or victim, you can bet a case would be a dark number of the crime. Indonesia despite having the Witness Protection Act and the Victims was enacted on August 11, 2006. But formally, this law is still considered to be maximal in regulating the protection of witnesses and Victims? How the position and role of statutory Act No.13 year 2006 about Protection of Witnesses and Victims? Are the barriers of protection of witnesses and crime victims in Indonesia according to Law 13 Year 2006 about Protection of Witnesses and Victims? In writing this research methode, the authors use the methode of empirical legal research and normative legal research methodes. The end result of this research was the discovery of the fact that the provision of witness protection and victim assistance crime by police and prosecutors are still lacking in practice. This is caused by several factors such as the protection is not known specifically in these two institutions. The absence of the unit that works specifically to provide protection to witnesses and victims in the structure in the structure of the Police and Prosecutor’s so protective measures undertaken by these two institutions is not optimal.Keywords: Witness, Protection, Victims